Profil Berpikir Logis Siswa SMP dalam Menyelesaikan Soal Asesmen Kompetensi Minimum (AKM) Numerasi Konten Aljabar - Hikamah, Lailatul; Kurniati, Dian; Oktavianingtyas, Ervin; Diah Sri Lestari, Nurcholif; Dwi Hary Jatmiko, Dhanar (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2025)
Logical thinking is the process of drawing conclusions based on facts through systematic steps and relevant arguments. This ability can be developed through mathematics learning, especially in problem-solving. This study aims to describe the logical thinking profile of junior high school students in solving AKM numeracy problems in algebra content.The research employs a descriptive method with a qualitative approach. The research instruments consist of two AKM numeracy problems related to systems of linear equations in two variables (SPLDV) and number patterns, as well as a validated semi-structured interview guide. Data were collected through a logical thinking test and interviews to identify indicators of logical thinking, namely coherence in reasoning, argumentation ability, and conclusion drawing. The test was administered to 30 eighth-grade students from SMP Negeri 1 Genteng. The results showed that two students met all indicators of logical thinking. These students were able to understand the problem by clearly writing down important information using their own words. They planned their solutions logically, applying the elimination and substitution methods for SPLDV problems and identifying number patterns in different ways. Their problem-solving steps aligned with Polya’s stages: understanding the problem, planning, implementing, and reviewing. Both students wrote conclusions supported by logical reasoning.